2013
DOI: 10.21098/bemp.v15i4.72
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Central Bank Independence on Price Stability: The Case of Indonesia

Abstract: This paper investigates the relationship between central bank independence (CBI) and inflation in Indonesia during 1970-2006. Using partial adjustment Ordinary Least Square (OLS) and Engel Granger Error Correction Model, the result shows that legal CBI index inversely affect the inflation, while the turnover of governor is not significant. This result emphasizes Bank Indonesia to strengthen its independency in order to achieve his inflation target. Keywords: Central bank independency, Inflation, Error Correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…According to Brumm (2002) and Andriani and Gai (2013), the absence of a negative relationship between CBI and inflation could be attributed to an inappropriate econometric methodology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Brumm (2002) and Andriani and Gai (2013), the absence of a negative relationship between CBI and inflation could be attributed to an inappropriate econometric methodology.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm that assuming a homogeneity co-efficient across countries, CBI does not explain inflation in developing countries. According to Brumm (2002) and Andriani and Gai (2013), the absence of a negative relationship between CBI and inflation could be attributed to an inappropriate econometric methodology.…”
Section: Resultsmentioning
confidence: 99%
“…The Governor's factor can be a determining factor for a Central Bank's competence, such as the results of research from Ozili (2020). Although Yessy Andriani and Prasanna Gai's analysis states that the Central Bank's independence will positively affect the inflation target, the Governor's change does not show any significance with the inflation target in Indonesia (Andriani & Gai, 2013). Changing a law must have a background and urgency.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The spread of COVID-19 has led the Indonesian Government to issue Law No. 2 2 of 2020 provides a basis for the Government, Financial Services Authority, Bank Indonesia and related parties to overcome the impact of the spread of COVID-9 on Indonesia's economy. Based on Law No.…”
Section: Introductionmentioning
confidence: 99%
“…Other research shows that there is a negative relationship between central bank independence and inflation in certain conditions, for example, improvement in institutional quality (Agoba et al, 2017;Bouoiyour & Selmi, 2013;Hove et al, 2017;Salahodjaev & Chepel, 2014). Other studies have found a negative relationship between the independence of central banks in developing countries (Andriani & Gai, 2013;Garriga & Rodriguez, 2019;Nagac & Rizvanoghlu, 2018). The diversity of the results of these studies, indicating the answer to the relationship between central bank independence and inflation is still a topic that continues to be discussed, and there is a research gap that has to be answered.…”
Section: Introductionmentioning
confidence: 97%